Associations of extracurricular physical activity patterns and body composition components in a multi-ethnic population of UK children (the Size and Lung Function in Children study): a multilevel modelling analysis - Lander S. M. M. Bosch; Jonathan C. K. Wells; Sooky Lum; Alice M. Reid (BMC, 2019)
Abstract Background Body Mass Index (BMI) is a common outcome when assessing associations between childhood overweight and obesity and physical activity patterns. However, the fat and fat-free components of BMI, measured by the Fat Mass Index (FMI) and Fat-Free Mass Index (FFMI), may show contrasting associations with physical activity, while ethnic groups may vary in both physical activity patterns and body composition. Body composition must therefore be evaluated when assessing the associations between childhood overweight and obesity and physical activity in multi-ethnic populations. Methods This cross-sectional study investigated associations of BMI, FMI and FFMI z-scores with extracurricular physical activity for 2171 London primary schoolchildren (aged 5-11 years) of black, South Asian and white/other ethnicity. Multilevel mixed-effects ordered logistic modelling was used, adjusting for age, sex and family and neighbourhood socioeconomic status as potential confounders. Results Controlling for ethnicity and individual, family and neighbourhood socioeconomic confounders, actively commuting children had significantly lower Odds Ratios for being in high BMI (Odds Ratio (OR) = 0.678; 95 % Confidence Interval (CI) = 0.531 − 0.865; p − value = 0.002) and FMI z-score groups (OR = 0.679; 95 % CI = 0.499 − 0.922; p = 0.013), but not FFMI z-score groups, than passive commuters. Children doing sports less than once a week had lower Odds Ratios for being in high BMI (OR = 0.435; 95 % CI = 0.236 − 0.802; p = 0.008) and FFMI (OR = 0.455; 95 % CI = 0.214 − 0.969; p = .041) z-score categories compared to daily active children. Differences in FMI between groups did not reach the significance threshold. A trend towards statistical significance was obtained whereby children's complete inactivity was associated with higher odds for being in higher BMI (OR = 2.222 : 95 % CI = 0.977 − 5.052; p = .057) and FMI z-score groups (OR = 2.485 : 95 % CI = 0.961 − 6.429; p = .060). FFMI z-scores did not show a similar trend with complete inactivity. Conclusions Active commuting was objectively associated with lower adiposity, while more frequent extracurricular sports participation was correlated with greater fat-free mass accretion. These relationships were independent of ethnicity and individual, family or neighbourhood socioeconomic confounding factors.